Untamed Shrews : Negotiating New Womanhood in Modern China - Yang, Shu, 1983- (Book collections on Project MUSE., 2023)
"Untamed Shrews traces the evolution of unruly women in Chinese literature, from the reviled "shrew" to the celebrated "new woman." Yang shows that the violent, jealous, and promiscuous shrew archetype of imperial times transformed into a symbol of empowerment in Republican and Communist China"--